2017
DOI: 10.1177/1087054717740632
|View full text |Cite
|
Sign up to set email alerts
|

Applied Machine Learning Method to Predict Children With ADHD Using Prefrontal Cortex Activity: A Multicenter Study in Japan

Abstract: A SVM using an objective index from RST may be useful as an auxiliary biomarker for diagnosis for children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 27 publications
0
60
0
1
Order By: Relevance
“…Comparing our results to other ML methods previously used to discriminate between ADHD and controls suggests that an ML model based on CPT data holds the promise of discriminating children with ADHD from controls, even when compared to more invasive or expensive approaches. For example, Yasumura et al ( 2017 ), who used near-infrared spectroscopy to quantify the change in prefrontal cortex oxygenated hemoglobin during reversed Stroop task, found an overall discrimination rate of 86.25%, with a sensitivity of 88.71% and a specificity of 83.78%. Likewise, using MRI data, Peng et al ( 2013 ) found an ADHD prediction accuracy of 90.18%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing our results to other ML methods previously used to discriminate between ADHD and controls suggests that an ML model based on CPT data holds the promise of discriminating children with ADHD from controls, even when compared to more invasive or expensive approaches. For example, Yasumura et al ( 2017 ), who used near-infrared spectroscopy to quantify the change in prefrontal cortex oxygenated hemoglobin during reversed Stroop task, found an overall discrimination rate of 86.25%, with a sensitivity of 88.71% and a specificity of 83.78%. Likewise, using MRI data, Peng et al ( 2013 ) found an ADHD prediction accuracy of 90.18%.…”
Section: Discussionmentioning
confidence: 99%
“…Availability and affordability of data collecting devices have opened doors for the use of ML to predict the likelihood of individuals developing a set of mental disorders such as depression, anxiety, autism, dementia, brain tumors, schizophrenia, psychosis, et cetera (Sen et al, 2018 ; Sakai and Yamada, 2019 ; Vieira et al, 2019 ). A growing number of supervised ML studies have been carried out on discriminating ADHD from control groups using the data obtained from electroencephalogram (EEG; Tenev et al, 2014 ), brain structural magnetic resonance imaging (MRI; Peng et al, 2013 ), MRI and functional magnetic resonance imaging (fMRI; Sen et al, 2018 ), Near-infrared spectroscopy (NIRS; Yasumura et al, 2017 ), and a combination of subjective and objective measures of ADHD (Emser et al, 2018 ). ML was also used to predict methylphenidate response in youth with ADHD using environmental, genetic, neuroimaging, and neuropsychological data (Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have used fNIRS in psychiatric disorders in children and adolescents, although ADHD is the most studied disorder [11][12][13]. Studies using fNIRS have focused on the differ-ence in hemodynamic activity according to the symptoms of ADHD or the prediction of treatment response to medications through various cognitive tasks.…”
Section: Attention-deficit/ Hyperactivity Disordermentioning
confidence: 99%
“…First, the examination of the differences in hemodynamic activity according to symptoms is based on the following principle: the core symptoms of ADHD (inattention, hyperactivity, and impulsivity) are related to executive function impairment and mainly reflect the function of the prefrontal cortex (PFC) [14][15][16]. Among the executive functions, impaired inhibition is frequently observed in children with ADHD in fNIRS studies using the stroop task, reverse stroop task (RST), or Go/No-Go task [11][12][13]17]. Negoro et al [13] reported that children with ADHD (ADHD group) showed significantly smaller changes in oxy-hemoglobin than typically developing children (TDC group) in the inferior lateral PFC bilaterally during the Stroop color-word task.…”
Section: Attention-deficit/ Hyperactivity Disordermentioning
confidence: 99%
“…Compared to traditional parametrical models, multivariate machine learning techniques are able to leverage high dimensional information simultaneously to understand how variables jointly distinguish between groups (Greenstein et al, 2012). In literature, support vector machine (SVM) is the most frequently applied machine learning classifier in neuroimaging data from children with ADHD, which has been aided by recursive feature elimination (RFE), temporal averaging, principle component analysis (PCA), fast Fourier transform (FFT), independent component analysis (ICA), 10-fold cross-validation (CV), hold-out, and leave-one-out cross-validation (LOOCV) techniques, to distinguish children with ADHD from normal controls (Brown et al, 2012; Chang et al, 2012; Cheng et al, 2012; Colby et al, 2012; Du et al, 2016; Fair et al, 2012; Iannaccone et al, 2015; Johnston et al, 2014; Sen et al, 2018; Yasumura et al, 2017). The commonly reported most important features (according to importance score) that contribute to successful group discrimination included functional connectivity of bilateral thalamus, functional connectivity, surface area, cortical curvature and/or voxel intensity in frontal lobe, cingulate gyrus, temporal lobe, etc.…”
Section: Introductionmentioning
confidence: 99%